Kinematic landing strategy transference in backward rotating gymnastic dismounts - Gittoes, M. J. R.; Irwin, G.; Kerwin, D. G. (Journal of Applied Biomechanics, 2013)
The aim of this study was to develop insight into the transference of kinematic landing strategies between backward rotating dismount skills. Female gymnasts performed backward rotating pike (N = 4 × 10 trials) and tuck dismounts skills (N = 4 × 10 trials) from the beam apparatus. Whole and lower body joint kinematic measures were quantified for the impact phase using an automatic motion analysis system (CODAMotion, Charnwood Dynamics Ltd.). Phase duration, whole body orientation and the mass center maximum z-displacement were similar (P < .01) between skills for individual gymnasts and the group. While skill differences in the hip joint motion profiles were notably larger (group root mean squared difference [RMSD]: 30.9%) than the ankle (group RMSD: 13.6%) and knee (group RMSD: 15.4%) joints, individual gymnast adjustments were made to the discrete joint kinematic measures. The use of a stable whole body orientation may provide important indicators of effective strategy transference between fundamental dismount skills. Further consideration of the joint strategy adjustments made according to the gymnast`s performance level may, however, be warranted.